MELANG LEARNING HOUSE AS A REVIEW OF COMMUNITY LITERACY STRENGTHENING IN ALOR DISTRICT - Niuflapu, Randi Nikanor; Neonufa, Samrid (Universitas Nusa Cendana, 2023)
This research is about the Rumah Belajar as a Place for Strengthening Community Literacy in the Melang Learning House which is a form of information facility and learning center for the surroundings in upgrading comprehension, expertness, knowledge, and reading skills as well as skills in managing Melang Learning House for the community. To know what kind of literacy strengthening is being used at the Rumah Belajar Melang. This research is descriptive with a qualitative approach. Data were collected by observation, interview, and see documents. This study uses qualitative data analysis which will be applied by researchers referring to Miles and Huberman's analytic concepts as follows: Data Collection, Data Reduction, Data Presentation, and Drawing Conclusions. The results of the study show that literacy-strengthening activities at the Melang Learning House include basic literacy (reading, writing, and speaking) and skills in processing agricultural products, waste, and used goods into goods of economic value.